2019
DOI: 10.1097/md.0000000000014894
|View full text |Cite
|
Sign up to set email alerts
|

Combined exposure of emotional labor and job insecurity on depressive symptoms among female call-center workers

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Most research on emotional demands and mental health has been conducted within specific occupations such as healthcare workers [ 13 , 14 , 15 ] and call center workers [ 16 , 17 ]. Even studies using national databases have typically been limited to subjects within the occupation categories of sales and service [ 9 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most research on emotional demands and mental health has been conducted within specific occupations such as healthcare workers [ 13 , 14 , 15 ] and call center workers [ 16 , 17 ]. Even studies using national databases have typically been limited to subjects within the occupation categories of sales and service [ 9 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Change-oriented OCB is future-oriented behavior with which an employee purports to improve one’s work methods or environment [13,14]. Of the three categories of outcomes, job insecurity’s negative relationships with employee health and well-being and attitudinal outcomes have been well established [7,15,16,17]. However, research has yielded conflicting findings on the link between job insecurity and performance and behavioral outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that the job strain of front-line employees in the electronic manufacturing industry is significantly higher than the average level of all industries in China (Zhang et al 2016 ) and research has highlighted that working conditions such as strenuous job demands and perceived job insecurity are associated with unhealthy mental states (Burgard et al 2009 ; Meltzer et al 2010 ; Kim and von Dem Knesebeck 2016 ; Cho et al 2019 ) with conditions exacerbated within the electronic industry (Shigemi et al 2000 ; Chen et al 2011 ; Lee et al 2015 ). In China, factory workers are vulnerable to symptoms of poor mental health and are often exposed to unfavorable psychosocial work environments, including perceived job insecurity, low levels of job control, and high levels of job demands (Sznajder et al 2014 ; Ji et al 2016 ; Huang et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%